All-Textile Compact Ultra-Wideband Microstrip Antenna with Full Ground Plane for WBAN Applications - Jinxin Du; Ruimeng Wang; Haiyan Li; Xue-Xia Yang; Christophe Roblin (International Journal of Antennas and Propagation)
A novel low-profile all-textile microstrip antenna for ultra-wideband (UWB) applications in wireless body area networks (WBANs) is presented. The antenna incorporates flexible materials such as felt and conductive fabrics which provide optimal wearing comfort and durability. The use of a single dielectric substrate layer facilitates the integration process. The antenna also features a full background plane that minimizes the back radiation towards the human body. Multiple branches are designed in a compact area to generate adjacent resonances, and their combination achieves broadband characteristics across the 4.83–9.57 GHz frequency band. The antenna has a miniaturized size of 60 mm × 60 mm, which is 1.6λg × 1.6λg (where λg represents the guided wavelength at the center frequency), and it has a high realized gain of up to 10 dBi. The fully grounded structure also ensures good isolation between the antenna and the human body, thereby alleviating concerns regarding safety and radiation degradation in WBAN context. Simulation results indicate that the antenna maintains high performance levels during various bending tests. Given its favourable properties like ultra-wide bandwidth, compact size, low profile, high flexibility, and low specific absorption rate (SAR), the proposed design could find broad application prospects in high-speed WBAN systems.